2010
DOI: 10.1097/ccm.0b013e3181ef45e2
|View full text |Cite
|
Sign up to set email alerts
|

Hypoproteinemia does not alter plasma volume expansion in response to a 0.9% saline bolus in awake sheep

Abstract: In contrast to our hypothesis, severe acute hypoproteinemia does not reduce plasma volume expansion in response to 50 mL/min 0.9% saline infusion in nonspleenectomized sheep when compared with the resultant plasma volume expansion after a 50 mL/min of 0.9% infusion in the euproteinemic state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The distribution and elimination of IV fluids have been investigated under the influence of inhalant anesthesia (36,38,42), various fluid infusion rates and duration (37,39), hemorrhage (41), hypoproteinemia (44), sepsis (34,40), and use of vasoactive agents (43,45) in sheep, rabbit, and pig models. Aside from the aforementioned studies performed by the same group of researchers, there is only one veterinary study that investigated real-time IV fluid dynamics using a different method in healthy anesthetized dogs (20).…”
Section: Previous Work In Animal Research Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution and elimination of IV fluids have been investigated under the influence of inhalant anesthesia (36,38,42), various fluid infusion rates and duration (37,39), hemorrhage (41), hypoproteinemia (44), sepsis (34,40), and use of vasoactive agents (43,45) in sheep, rabbit, and pig models. Aside from the aforementioned studies performed by the same group of researchers, there is only one veterinary study that investigated real-time IV fluid dynamics using a different method in healthy anesthetized dogs (20).…”
Section: Previous Work In Animal Research Modelsmentioning
confidence: 99%
“…This study also revealed that markedly supraphysiologic infusion doses exceed the limits of linearity of a VK model. In 2010, Brauer et al (44) found that severe acute hypoproteinemia induced by plasmapheresis does not reduce the PV expansion of isotonic crystalloid infusion (27 mL/kg 0.9% NaCl over 20 min) in non-hemorrhaged, non-splenectomised sheep. The depletion of mean total protein concentration from 5.4 to 2.5 g/dL following plasmapheresis resulted in a parallel reduction in mean plasma COP from 20 to 9.6 mmHg (44).…”
Section: Previous Work In Animal Research Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the level of protein inside the vessels falls, as during trauma and surgery, it implies further shifting of fluid out of the vasculature. Smaller molecules, such as crystalloids, are probably not much effected since they escape through the barrier anyway 20,21 . During normal conditions it will, however, only lead to a moderate shift and accumulation of fluid since both an increased lymph flow and interstitial hydrostatic pressure in combination with diluted amount of interstitial protein will limit any excess accumulation of fluid interstitially.…”
Section: Interstitiummentioning
confidence: 99%
“…Smaller molecules, such as crystalloids, are probably not much effected since they escape through the barrier anyway. 20,21 During normal conditions it will, however, only lead to a moderate shift and accumulation of fluid since both an increased lymph flow and interstitial hydrostatic pressure in combination with diluted amount of interstitial protein will limit any excess accumulation of fluid interstitially. During normal circumstances there is also an escape of albumin of about 5% of the intravascular albumin rate per hour.…”
Section: N T E R S T I T I U Mmentioning
confidence: 99%